The creative screenwriter exercises to expand your craft - Waldeback, Zara; Batty, Craig (Methuen Drama, 2012)
The film industry is seeking fresh screenwriting talent, but today's writers don't just need to be accomplished at their craft - they need to be highly creative. 'The Creative Screenwriter' is a workbook of inspiring writing exercises to sharpen the writer's talents.